The fungal literature-based occurrence database for southern West Siberia (Russia) - Filippova, Nina; Ageev, Dmitry; Bolshakov, Sergey; Davydov, Evgeny; Filippova, Aleksandra; Filippov, Ilya; Gashkov, Sergei; Gorbunova, Irina; Kalinina, Ludmila; Kudashova, Nadezhda; Palomozhnykh, Ekaterina; Shabanova, Natalia; et al. (Biodiversity data journal, 2021)
The paper presents the initiative on literature-based occurrence data mobilisation of fungi and fungi-related organisms (literature-based occurrences, Darwin Core MaterialCitation) to develop the Fungal literature-based occurrence database for the southern West Siberia (FuSWS). The initiative on mobilisation of literature-based occurrence data started in the northern part of West Siberia in 2016. The present project extends the initiative to the southern regions and includes ten administrative territories (Tyumen Region, Sverdlovsk Region, Chelyabinsk Region, Omsk Region, Kurgan Region, Tomsk Region, Novosibirsk Region, Kemerovo Region, Altai Territory and Republic of Altai). The area occupies the central to southern part of the West Siberian Plain and extends for about 1.5 K km from the west to the east from the eastern slopes of the Ural Mountains to Yenisey River and from north to south—about 1.3 K km. The total area equals about 1.4 million km 2 . The initiative is actively growing in spatial, collaboration and data accumulation terms. The working group of about 30 mycologists from eight organisations dedicated to the data mobilisation was created as part of the Siberian Mycological Society (informal organisation since 2019). They have compiled the almost complete bibliographic list of mycology-related papers for the southern West Siberia, including over 900 publications for the last two centuries (the earliest dated 1800). All literature sources were digitised and an online library was created to integrate bibliography metadata and digitised papers using Zotero bibliography manager. The analysis of published sources showed that about two-thirds of works contain occurrences of fungi for the scope of mobilisation. At the time of the paper submission, the database had been populated with a total of about 8 K records from 93 sources. The dataset is uploaded to GBIF, where it is available for online search of species occurrences and/or download. The project's page with the introduction, templates, bibliography list, video-presentations and written instructions is available (in Russian) at the web site of the Siberian Mycological Society. The initiative will be continued in the following years to extract the records from all published sources. The paper presents the first project with the aim of literature-based occurrence data mobilisation of fungi and fungi-related organisms in the southern West Siberia. The full bibliography and a digital library of all regional mycological publications created for the first time includes about 900 published works. By the time of paper submission, nearly 8 K occurrence records were extracted from about 90 literature sources and integrated into the FuSWS database published in GBIF.